Inhibition of ghrelin action in vitro and in vivo by an RNA-Spiegelmer - Helmling, Steffen (National Academy of Sciences, 2004)
Employing in vitro selection techniques, we have generated biostable RNA-based compounds, so-called Spiegelmers, that specifically bind n-octanoyl ghrelin, the recently discovered endogenous ligand for the type 1a growth hormone secretagogue (GHS) receptor. Ghrelin is a potent stimulant of growth hormone release, food intake, and adiposity. We demonstrate that our lead compound, l-NOX-B11, binds ghrelin with low-nanomolar affinity and inhibits ghrelin-mediated GHS-receptor activation in cell culture with an IC(50) of 5 nM. l-NOX-B11 is highly specific for the bioactive, n-octanoylated form of ghrelin. Like the GHS receptor, it does not recognize the inactive unmodified peptide and requires only the N-terminal five amino acids for the interaction. The i.v. administration of polyethylene glycol modified l-NOX-B11 efficiently suppresses ghrelin-induced growth hormone release in rats. These results demonstrate that the neutralization of circulating bioactive ghrelin leads to inhibition of ghrelin's secretory effects in the CNS.